Alloreactive regulatory T cells generated with retinoic acid prevent skin allograft rejection. Issue 2 (2nd December 2014) - Moore, Carolina; Tejon, Gabriela; Fuentes, Camila; Hidalgo, Yessia; Bono, Maria R.; Maldonado, Paula; Fernandez, Ricardo; Wood, Kathryn J.; Fierro, Juan A.; Rosemblatt, Mario; Sauma, Daniela; Bushell, Andrew
<x xml:space="preserve">Abstract</x> CD4+CD25+Foxp3+ regulatory T (Treg) cells mediate immunological self‐tolerance and suppress immune responses. Retinoic acid (RA), a natural metabolite of vitamin A, has been reported to enhance the differentiation of Treg cells in the presence of TGF‐β. In this study, we show that the co‐culture of naive T cells from C57BL/6 mice with allogeneic antigen‐presenting cells (APCs) from BALB/c mice in the presence of TGF‐β, RA, and IL‐2 resulted in a striking enrichment of Foxp3+ T cells. These RA in vitro‐induced regulatory T (RA‐iTreg) cells did not secrete Th1‐, Th2‐, or Th17‐related cytokines, showed a nonbiased homing potential, and expressed several cell surface molecules related to Treg‐cell suppressive potential. Accordingly, these RA‐iTreg cells suppressed T‐cell proliferation and inhibited cytokine production by T cells in in vitro assays. Moreover, following adoptive transfer, RA‐iTreg cells maintained Foxp3 expression and their suppressive capacity. Finally, RA‐iTreg cells showed alloantigen‐specific immunosuppressive capacity in a skin allograft model in immunodeficient mice. Altogether, these data indicate that functional and stable allogeneic‐specific Treg cells may be generated using TGF‐β, RA, and IL‐2. Thus, RA‐iTreg cells may have a potential use in the development of more effective cellular therapies in clinical transplantation.